Precision machining with a vibration device - Rui, Zhao Ya. (2008)
This dissertation studies grinding of single-crystal Si with a vibration device. Si samples were cut from (100) silicon wafer. The vibration device was employed to hold the sample. The device was placed on the grinding machine table. The grinding direction is parallel to [110] direction of (100) silicon. These samples were subjected to grinding with different vibration directions, frequencies and amplitudes under the same experimental conditions. The surface roughness and the surface texture of all samples were analyzed. Samples ground with vibrations showed better surface roughness values on the silicon surfaces, compared with surfaces ground without vibrations.